The realtionship between feeding patterns and stunting incidence in toddlers aged 0-24 months at the Cicangkang Girang Primary Health Care - R Noucie Septriliyana; Dessy Aryanti (Science Midwifery, 2022)
Stunting is one of the indicators of chronic nutritional status due to insufficiency of food intake for a long time, with poor food quality. The rank of West Java is 23rd out of 35 provinces, inciden of stunting in West Java there are 2.7 million toddlers or 29.9% affected by stunting. Primary Health Care Cicangkang Girang is one of the the highest incidence of stunting in KBB (17.49%). Stunting is one of the indicators of chronic nutritional status due to insufficiency of food intake for a long time, with poor food quality. This study aims to determine the relationship between feeding patterns and the incidence of stunting in toddlers. The method in this study uses an analytical correlation design using a cross sectional approach. The sample in this study was taken using a random sampling technique on toddlers aged 0-24 months who suffered from stunting, with a total of 110 respondents. Data analysis was carried out univariately and bivariately with chi square test. The results of this study found that 59 (53.6%) babies got an improper feeding pattern, 90 (81.8%) babies got a short stunting condition. The results of the analysis obtained a p value of 0.002 ≤ α (0.05), meaning that there was a significant relationship between feeding patterns and the incidence of stunting in toddlers. Higly recommended that Primary Health Care can provide health education to all the public about feeding patterns to toddlers according to the standards of the Ministry of Health of the Republic of Indonesia.